Enhanced future changes in wet and dry extremes over Africa at convection-permitting scale - Elizabeth J. Kendon (Nature Portfolio, 2019)
For the first time, climate change experiments with a convection-permitting model have been carried out over an Africa-wide domain. These show more severe future changes in both wet and dry extremes over Africa compared to a traditional coarser resolution climate model.